2021
DOI: 10.1542/peds.2021-051378
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Subsequent Mental Health, Substance Use, and Well-being in Young Adults

Abstract: OBJECTIVES Discrimination has been shown to have profound negative effects on mental and behavioral health and may influence these outcomes early in adulthood. We aimed to examine short-term, long-term, and cumulative associations between different types of interpersonal discrimination (eg, racism, sexism, ageism, and physical appearance discrimination) and mental health, substance use, and well-being for young adults in a longitudinal nationally representative US sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…Finally, our study was cross sectional, which limits the directional interpretability of our findings. However, recent longitudinal research has confirmed the directionality of effect from cultural humility to working alliance and therapy outcomes (Dixon et al, 2022) and the directionality from experiences of perceived discrimination to mental and physical health concerns across BIPOC samples has also been established (e.g., Lei et al, 2021). Given these prior studies that support the order of variables in our model, as well as the assertion that tests of indirect effects with cross-sectional data can still be appropriate for examining emerging theoretical relationships among variables (Spector, 2019), our empirically and theoretically informed model seemed suitable to test in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, our study was cross sectional, which limits the directional interpretability of our findings. However, recent longitudinal research has confirmed the directionality of effect from cultural humility to working alliance and therapy outcomes (Dixon et al, 2022) and the directionality from experiences of perceived discrimination to mental and physical health concerns across BIPOC samples has also been established (e.g., Lei et al, 2021). Given these prior studies that support the order of variables in our model, as well as the assertion that tests of indirect effects with cross-sectional data can still be appropriate for examining emerging theoretical relationships among variables (Spector, 2019), our empirically and theoretically informed model seemed suitable to test in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…17 Racial discrimination has been associated with a number of negative mental health consequences, including high reported stress, increased psychiatric diagnoses and substance use, and poor reported overall health. 18 Mental health disorders associated with Black youth are worsening; Centers for Disease Control and Prevention data show that the rate of suicide attempts among Black adolescents rose 73% from 1991 to 2017. 19 Comprehensive solutions that identify at-risk children and adolescents, such as hospital-based violenceintervention programs, can provide Black patients with immediate support to mitigate the compounded mental health sequelae of firearm injuries in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health disorders in the US have disproportionately affected Black children and adolescents . Racial discrimination has been associated with a number of negative mental health consequences, including high reported stress, increased psychiatric diagnoses and substance use, and poor reported overall health . Mental health disorders associated with Black youth are worsening; Centers for Disease Control and Prevention data show that the rate of suicide attempts among Black adolescents rose 73% from 1991 to 2017 .…”
Section: Discussionmentioning
confidence: 99%
“…Racialized group status might also be related to flourishing. Evidence indicates that chronic exposure to frequent interpersonal and systemic stressors puts Hispanic or Latino, Black or African American and members of other racially minoritized groups at higher risk of poor mental health such as depression (Huynh & Fuligni, 2010;Sirin et al, 2015;Williams et al, 2003), and findings from a recent study indicates that higher frequency of everyday discrimination is related to lower odds of flourishing (Lei et al, 2021).…”
Section: Prevalence and Correlates Of Young Adult Flourishingmentioning
confidence: 99%
“…While the evidence suggests that positive mental health is related to demographic characteristics such as age, gender, racialized group and ethnicity and proximal experiences such as educational engagement, supportive social relationships, civic engagement, discrimination and physical health (de la la Fuente et al, 2020;Fenn et al, 2021;Keyes, 2006;Keyes et al, 2012;Lei et al, 2021;O'Connor et al, 2017), little is known about the prevalence of flourishing among a nationally representative sample of US young adults, changes from adolescence into young adulthood and how proximal indicators of healthy development are related to flourishing among young adults in the United States. The present study aims to expand upon Keyes (2006) prior examination of the state of positive mental health among US adolescents by describing those same adolescents when they became young adults.…”
Section: The Current Studymentioning
confidence: 99%